EVALUASI PENCAPAIAN STANDAR KOMPETENSI MAHASISWA PPL PROGRAM PPKHB PENJAS UNY TAHUN 2011 - Ngatman Ngatman (Jurnal Pendidikan Jasmani Indonesia, 2013)
This study aimed to evaluate the extent of achievement of competency standards PPL PPKHB sports and healtheducation UNY students in 2011. This study is expected to be used as PPKHB sports and health education PPLstudent evaluations. For relevant agencies such as the Faculty of Sport in particular study program Physical Education,Health and Recreation may be used as consideration to improve the quality of its students in order to have adequateprovision to be professional educators. This study is a quantitative descriptive study using survey method of datacollection instruments such as questionnaires. The population in this study was student PPL PPKHB sports and healtheducation UNY 2011 in SD Magelang regency. The subjects in this study were 90 students PPKHB sports and healtheducation the PPL in SD Magelang regency. The instrument in this study used a questionnaire or a questionnairehas been prepared by Joko Tri Kristiyanto, by having a reliability coefficient of 0.922 and a questionnaire has beendeclared invalid. Analysis using descriptive analysis set forth in the form of a percentage. The results showed thatthe level of student achievement of competency standards PPL sports and health education UNY PPKHB Programin 2011 in Magelang District elementary sufficient in the category. More detailed level of student achievement ofcompetency standards PPKHB sports and health education can be described as follows: 12 students (13.3 %) incategory, 65 students (72.2 %) in enough categories, and 13 students (14.5 %) in the category of less. From theresults of these studies are the most prominent competence Pedagogic competence as many as 12 students (13.3%). It can be concluded that the level of student achievement of competency standards PPL PPKHB sports andhealth education UNY 2011 in SD Magelang District has sufficient competence.Keywords: Evaluation, Standards of Competence, PPL, PPKHB Program.